The first febrile seizure; predisposing factors and recurrence rate - Kazemi, Alinaghi; Badv, Reza Shervin; Fallah, Ramazan; Piri, Ali; Tahernia, Leila; Vafaee shahi, Mohammad (Iranian Journal of Child Neurology, 2021)
Objective Febrile seizure is the most common worrisome neurologic disorder in children in terms of parental point of view. The purpose of this study was to answer distressing parents’ questions about the prevalence and possibility of febrile seizure recurrence. Materials & Methods 140 patients who were admitted due to the first febrile seizure in the six months (March up to September) of the year 2015 were enrolled to this study. Exclusion criteria include central nervous system infection, non-confirmed febrile seizure and lack of parental acceptance for long-term inclusion in this study. All children were followed in terms of second febrile seizure during one year follow-up from the time of first febrile seizure. (3 sentences were deleted). Results Recurrence of febrile seizure was 25.7 % during one-year follow-up. Significant risk factors for recurrence include: age less than one year old, male gender, seizure with low level of fever, family history of epilepsy, family history of febrile seizure, complex febrile seizure (focal and repeated in 24 hours), seizure duration more than 15 minutes and parental indifference to the onset of fever in their children before seizure occurrence. Although duration of fever before seizure, failure to thrive, positive history of admission in neonatal period, dystocia at birth delivery and children with day care staying were associated with greater febrile seizure recurrence; but, they did not have significant relationship with recurrence rate. Prophylaxis with benzodiazepine reduced the recurrence rate. Conclusion Chance of febrile seizure recurrence in one-year follow-up increased in presence of risk factors expressed in finding part. parental indifference to the onset of fever in their children that is starting before seizure was a considerable risk factor in terms of recurrence prevalence. We recommended to emphasis on parental education about this new finding as a risk factor for febrile seizure in order to prevent its future recurrence.